Development and validation of serological markers for detecting recent Plasmodium vivax infection - Longley, Rhea J.; White, Michael T.; Takashima, Eizo; Brewster, Jessica; Morita, Masayuki; Harbers, Matthias; Obadia, Thomas; Robinson, Leanne J.; Matsuura, Fumie; Liu, Zoe S. J.; Li-Wai-Suen, Connie S. N.; Tham, Wai-Hong; et al. (Nature Medicine, 2020)
A major gap in the Plasmodium vivax elimination toolkit is the identification of individuals carrying clinically silent and undetectable liver-stage parasites, called hypnozoites. This study developed a panel of serological exposure markers capable of classifying individuals with recent P. vivax infections who have a high likelihood of harboring hypnozoites. We measured IgG antibody responses to 342 P. vivax proteins in longitudinal clinical cohorts conducted in Thailand and Brazil and identified candidate serological markers of exposure. Candidate markers were validated using samples from year-long observational cohorts conducted in Thailand, Brazil and the Solomon Islands and antibody responses to eight P. vivax proteins classified P. vivax infections in the previous 9 months with 80% sensitivity and specificity. Mathematical models demonstrate that a serological testing and treatment strategy could reduce P. vivax prevalence by 59–69%. These eight antibody responses can serve as a biomarker, identifying individuals who should be targeted with anti-hypnozoite therapy. Plasmodium vivax can cause a clinically silent liver-stage infection that can reactivate, triggering blood-stage disease. A new test measuring antibody responses can identify P. vivax carriers for targeted treatment intervention.